The Impact of Practice Effects on NSSI Stroop Task Reaction Times - Kostreva, Mckenzie; Owens, Carley A.; Hagan, Christopher R.; Muehlenkamp, Jennifer J. (My University, 2019)
Non-Suicidal Self Injury (NSSI) is the deliberate harm to one’s body without the intent to die. College aged students experience high levels of stress and are prone to engage in NSSI. The NSSI Stroop Task is a test that can be used to observe the attentional bias towards emotional stimuli by using stimuli specific words (e.g., alone) with neutral words (e.g., museum ; Cha et al., 2010). The Stroop Task measures the time it takes an individual to respond to a target word when exposed to words related to a specific topic. The Stroop Task is measured by subtracting the time lapse for neutral words compared to stimuli specific words, in which the larger difference in time, is translated into greater interference. Practice effects, or repeating a test, also impact the validity of a test by possibly improving exam score and/or decreasing response time. This study will observe if practice effects impact the NSSI Stroop Task.
Color poster with text, charts, and graphs.
Keywords: Non-suicidal self-injury; Stroop Task; Posters